1997
DOI: 10.1007/bf02479908
|View full text |Cite
|
Sign up to set email alerts
|

Experimental glomerulonephritis induced by a low dose of anti-thy-1 antibody

Abstract: Background: Thy-1.1 nephritis is a widely used model of proliferative glomerulonephritis. Lesions are characterized by diffuse mesangiolysis and prominent ballooning of capillary loops, followed by severe mesangial proliferation. However, such severe lesions are not common in human mesangial proliferative nephritis. We analyzed mild-to-moderate mesangial proliferative nephritis induced by a lower dose of anti-Thy-1.1 antibody. Methods" We administered a low intravenous dose (0.02 mg/mL) of antibody to Wistar r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2002
2002

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This observation is consistent with a previous report by K. Muroga et al . They demonstrated that chronic nephritis can be induced by using a high‐dose antibody and that reduced volume of antibody failed to induce glomerulonephritis34. Also, the small dose of antibody used in this study did not lead to any inducement in apparent damage to glomeruli, as shown in Figure 2.…”
Section: Discussionmentioning
confidence: 50%
“…This observation is consistent with a previous report by K. Muroga et al . They demonstrated that chronic nephritis can be induced by using a high‐dose antibody and that reduced volume of antibody failed to induce glomerulonephritis34. Also, the small dose of antibody used in this study did not lead to any inducement in apparent damage to glomeruli, as shown in Figure 2.…”
Section: Discussionmentioning
confidence: 50%
“…We studied an experimental model of mild-degree Thy-1 nephritis with a small dose of the antibody [35]. We administered a 1/10 dose of anti-thy 1.1 monoclonal anti-body(OX-7) to Wistar rats, comparing the results with ordinary experimental dosages.…”
Section: Glomerular Injury and Capillary Repairmentioning
confidence: 99%